Impact of Ethanolic Spice Extracts and Sodium Benzoate on the Physicochemical Properties and Health-Related Quality of Watermelon Juice - Md. Esrafil; Pratima Roy Dina; Nishita Pondit; Eity Akter; Maymuna Faruk Trisha; Mahmuda Khatun; Nargis Akter; Md. Abdul Alim; Syeda Huraiya Hasan Nishi; Md. Abu Zubair (Knowledge Dynamics, 2024)
Background: Watermelon juice is a refreshing drink to quench the extreme tropical heat thirst. Packed with simple carbs, antioxidants, vitamins, and minerals, it boosts immunity and aids in the body's recovery from dehydration. Moreover, it’s a delicious and filling drink. A study was carried out to investigate the effects of ethanolic extracts on watermelon juices. Methods: Physicochemical changes such as total soluble solid, vitamin C, acidity, pH, non-enzymatic browning reaction, sensory evaluation, and total viable count were measured at 7-day intervals over 28 days. Results: The findings showed that clove and sodium benzoate had a greater effect on unpasteurized juice than black pepper and sodium benzoate on pasteurized juice. Clove and sodium benzoate outperformed the others in unpasteurized juice. For unpasteurized and pasteurized juice, black pepper and sodium benzoate showed greater results than others. Besides, sodium benzoate (3.10×102, 1.2×102, 0×102, and 1.0×102) and cinnamon (4.0×102, 2.2×102, 3.0×102 and 2.0×102) presented better antimicrobial activity than others for unpasteurized juice. Sodium benzoate (3.0×102, 1.10×102, 0×102, and 2.0×102) and black pepper (1.20×102, 2.1×102, 2.0×102, and 1.10×102) displayed better antimicrobial activity than others for pasteurized juice. For both unpasteurized and pasteurized juice, cinnamon and sodium benzoate were comparatively more popular than others. Conclusions: Based on the findings, these extracts could be employed as natural antimicrobial preservatives instead of artificial preservatives in watermelon juice to increase its shelf life.